Eagle Syndrome - the issue of an elongated styloid process. A literature review - Martyna Brzoza; Bartosz Dubniański; Julia Stawińska-Dudek; Wiktoria Józefowicz; Damian Machaj (Journal of Education, Health and Sport)
Introduction and purpose: